4 Stat. at Large of S.C. 343-44 (1838) - (:unkn) unknown (My University, 1776)
An Act to Prevent Sedition, and Punish Insurgents and Disturbers of the Public Peace, § 1: Prohibited any person to “take up arms with a hostile intent.”
Keywords: CARRY - INTENT TO COMMIT CRIME